The importance of the pharmacist in consulting pediatric patients using off-label medications (Research, Society and Development, 2021)
Medicines play a fundamental role in the recovery and maintenance of health, and must be safe, effective, quality and accessible to the patient. The pharmaceutical consultation for pediatric patients using off-label drugs whose use is different from that described on their label or package insert, when it comes to indication, route of administration, dosage and age group, has the role of assisting in pharmacotherapy , minimizing errors and adverse drug reactions indicated by physicians and preventing drug-related problems (PRM's). The administration of medications from adults to children is a common practice that should be treated with caution, as the child's physiology is different and the risks of intoxication are diverse. The aim of this study was to highlight the importance of the pharmacist in the pharmacotherapeutic monitoring of pediatric patients using off-label medications during pharmaceutical consultations. The search took place in the database of the Latin American and Caribbean Literature in Health Sciences (LILACS) and in the Scientific Electronic Library Online (SciELO). To delimit the contents, inclusion criteria were used: articles available in full in Portuguese and English, in the period from 2012 to 2021 with free access and that were relevant to the theme. The results showed that the pharmacist is essential in the monitoring and guidance of patients who use off-label drugs, requiring the proper training of this professional on the subject. In this context, the pharmacist appears as a professional who promotes the correct use of drugs in pediatrics, contributing to safe pharmacotherapy.